The Role of Expansion Movement in the Establishment of New Region in Indonesia: A Study of Parigi Moutong Regency - Alamsyah, Muhammad Nur; Subekti, Valina Singka (Komunitas, 2017)
The study explains the dimension of the structure of resource mobilization in the political movement of new region establishment in Indonesia. The establishment of new regions has been seen only in the utilization of formal structures. In fact, the involvement of non-formal organizations also contributes to the importance and determines a region expansion. The study employed a qualitative approach with the support of primary and secondary data related to the establishment of Parigi Moutong Regency. The data was obtained through in-depth interviews with the group figures of the expansion. The secondary data was obtained from mass media and government agencies as well as personal documentation. The theory used was the dimension of the resource mobilization structure of the political opportunity structure (POST) theory. The study reveals that the success of the expansion movement in Parigi Moutong Regency for their structure resource mobilization by civil society organizations or non-formal to formal institutional build up pressure by using lobbying based on personal, professional and primordial networks. The influence of national political reforms motivated and mobilized the mobilization of movement resources as a repetition of the movement that had taken place in the previous expansion movement in Parigi Moutong Regency.